Capacidade combinatória de linhagens e seleção de híbridos de sorgo sacarino - Rocha, Mara Jane da (2016)
Sweet sorghum figure as an alternative feedstock for ethanol production. The establishment of this culture in Brazilian production chain depends on the development of more productive and adapted cultivars. The aim of this study was to evaluate the general combining ability (GCA) of sweet sorghum lines and specific combining ability (SCA) of hybrid combinations as the agronomic and technological traits, and additionally to identify promising hybrid combinations for evaluation in advanced trials. Five restorer lines (R) and four male-sterile lines (A) were used in a partial cross diallel yielding 20 hybrids. The parental lines, hybrids and one check were evaluated in experiments carried out in a rectangular lattice design 5x6 with three replicates in two locations. The following traits were measured: flowering time, plant height, green mass yield, dry matter percentage, dry matter yield, juice extraction, total soluble solids content, sucrose content, purity, reducing sugars content, fiber content, sugars reducing total content, total recoverable sugars, hydrous ethanol, tons of per hectare, and ethanol production. There were differences between locations and genotypes for the traits. There was a significant effect of the genotype by environment interaction for most characters, except juice extraction, purity and reducing sugars content. There were a significant effect of GCA and SCA for most traits, indicating that additive and non-additive effects affect the phenotypic expression. Considering the effects of the GCA, the A line 201402B022-A, and R lines BRS 511, CMSXS643, and CMSXS646 were considered promising for exploration as parents in breeding programs of sweet sorghum in order to increase the ethanol production and the quality of the feedstock.The hybrids 201402B010-A x BRS 511, 201402B010-A x BRS 508, 201402B010-A x CMSXS646, 201402B022-A x BRS 511, 201402B022-A x CMSXS643, 201402B022-A x CMSXS646, 201402B022-A x CMSXS647 were the most promising for ethanol yield.